Motivation of Student Toward Politics: A Study of Tribhuvan University Campus (Research Nepal Journal of Development Studies, 2023)
This article is based on the study conducted in Tribhuban University for the MPhil degree. This study was conducted to find out student’s motivation towards politics, their contribution in academic improvements and shaping the larger countries academic progress. To fulfil this questions, qualitative methods was applied. Data were collected through in-depth interview and case stories. The total three case stories and 15 interviews were taken. Main argument of the article is Free Student Union (FSU) leadership have been concerned with party politics rather academic improvements. This show the overall image of Nepal’s FSU’s looking glass self. There are several motivational factors of the student leaders being engaged in politics. Family background, Political situations, peer groups, institutional effects, class and ideology. Most of them have begun their political affiliation and activities from their school life and few of them have joined the politics at the colleges, where from they were ideologically motivated or were embraced by the political movement of the time.